Smoking History as The Main Factors of Chronic Kidney Disease in Hemodialytic Patients - Trisnawati, Aprilia; Sari, Yeni Kartika; Nurmawati, Thatit; Ta'adi, Ta'adi (IJNP (Indonesian Journal of Nursing Practices), 2024)
Background: The high risk of death and treatment costs for chronic kidney disease make a global problem. History of hypertension, diabetes mellitus, smoking, and energy supplement drinks are factors that cause chronic kidney disease that can be controlled. Consequently, it is important to identify factors associated with poor outcomes among hemodialytic patients.Objective: This study aims to determine the main factors associated with chronic kidney disease in a private hospital in Blitar.Methods: The study was a cross-sectional study. 132 patients were purposively selected in the study. Data was analyzed using logistic regression.Results: The multivariate analysis showed that a smoking history accompanied by another factor increases the risk of Chronic Kidney Disease.  Diabetes Mellitus history (OR: 3.04), Hypertension history (OR: 1,4), Smoking History (OR:0,3), Drinking energy supplement history (OR:0.3) were significant variables on patients undergoing maintenance hemodialyis.Conclusions: The foremost common cause of patients undergoing maintenance hemodialysis is smoking history. More education is needed for society to avoid chronic kidney disease by exercising health control regularly, stopping smoking, and having a healthy lifestyle.